Attributing physical and biological impacts to anthropogenic climate change - Rosenzweig, Cynthia; Karoly, David; Vicarelli, Marta; Neofotis, Peter; Wu, Qigang; Casassa, Gino; Menzel, Annette; Root, Terry L.; Estrella, Nicole; Seguin, Bernard; Tryjanowski, Piotr; Liu, Chunzhen; et al. (Nature, 2008)
Significant changes in physical and biological systems are occurring on all continents and in most oceans, with a concentration of available data in Europe and North America. Most of these changes are in the direction expected with warming temperature. Here we show that these changes in natural systems since at least 1970 are occurring in regions of observed temperature increases, and that these temperature increases at continental scales cannot be explained by natural climate variations alone. Given the conclusions from the Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment Report that most of the observed increase in global average temperatures since the mid-twentieth century is very likely to be due to the observed increase in anthropogenic greenhouse gas concentrations, and furthermore that it is likely that there has been significant anthropogenic warming over the past 50 years averaged over each continent except Antarctica, we conclude that anthropogenic climate change is having a significant impact on physical and biological systems globally and in some continents. Climate change: Human influence tracked Many natural biological and physical systems are undergoing changes consistent with a gradual rise in temperature. Such changes have occurred on all continents and in most oceans since at least 1970. An Article in this issue is the first to formally link the observed changes to human-induced climate change. The study is a meta-analysis that uses a larger database than the recent IPCC report, and it takes account of land-use change and other complications. The authors conclude that anthropogenic climate change is affecting physical and biological systems globally. But as Francis Zwiers and Gabriele Hegerl point out in News & Views, this proof based on the principle of joint attribution stops short of the statistical certainty that would be provided by 'end-to-end' models linking human activity directly to the observed changes, rather than via effects on the climate system. Natural physical and biological systems change in regions of temperature increase. Such changes have occurred on all continents and in most oceans since at least 1970. This paper presents statistical evidence that these changes cannot be explained by natural climate variations alone, and concludes that anthropogenic climate change is affecting physical and biological systems globally and on some continents.